Relationship between facial symmetry and perceived health and attractiveness, with a test of the ability of Homo sapiens to discriminate facial symmetry across species - Chua, Sok Hoon (2009)
Past research suggest that facial symmetry is as an honest indicator of the biological fitness of the organism, and more symmetrical faces were consistently found to be perceived as more attractive and healthier. However, most studies had focused from an intraspecies perspective. Therefore, it was of interest to test if previous findings remain true when carried out from an interspecies perspective. Effect of the degree of genetic differences between the perceiver and the perceived targets on humans’ perception of attractiveness and health was also examined. Support was found for the relationship between facial symmetry and perceived attractiveness, but not for perceived health. Difference in phylogenetic distances was not found to have an influence on participants’ perception of attractiveness and health. Implications of the role of facial symmetry as an indicator of biological fitness were discussed.